2006
DOI: 10.1211/jpp.58.6.0012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of formulation excipients on human intestinal transit

Abstract: The accelerating effect of polyethylene glycol 400 on small intestinal transit has been previously reported. The aim of this study was to investigate the influence of other solubility-enhancing excipient, propylene glycol, D-alpha-tocopheryl-polyethylene glycol-1,000 succinate (VitE-TPGS) and Capmul MCM, on human intestinal transit. A 5-g dose of each excipient was administered to seven healthy male subjects. Propylene glycol and VitE-TPGS were administered dissolved in 150 mL water. Capmul MCM was administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…A meta-analysis by Davis et al (1) using data pooled from 201 dosage form administrations puts the average residence time in the small intestine at 3 h irrespective of dosage form type (tablets, liquids or pellets), and similar average values have been reported by more recent studies (2)(3)(4). The ability of drugs (5)(6)(7) or excipients (8)(9)(10)(11)(12)(13) to modulate intestinal transit is known, but the presence of food is thought to be negligible (1). However, the Davis metaanalysis and the majority of other studies only consider two feeding regimens: (1) fasted in which the dosage form is given on an empty stomach with food withheld for a number of hours or (2) fed in which the formulation is taken after food.…”
Section: Introductionmentioning
confidence: 73%
“…A meta-analysis by Davis et al (1) using data pooled from 201 dosage form administrations puts the average residence time in the small intestine at 3 h irrespective of dosage form type (tablets, liquids or pellets), and similar average values have been reported by more recent studies (2)(3)(4). The ability of drugs (5)(6)(7) or excipients (8)(9)(10)(11)(12)(13) to modulate intestinal transit is known, but the presence of food is thought to be negligible (1). However, the Davis metaanalysis and the majority of other studies only consider two feeding regimens: (1) fasted in which the dosage form is given on an empty stomach with food withheld for a number of hours or (2) fed in which the formulation is taken after food.…”
Section: Introductionmentioning
confidence: 73%
“…It is known that some excipients and vehicles, such as polyethylene glycol 400 (PEG 400), mannitol and xylitol, among others, may decrease the GI transit time, resulting in decreased drug bioavailability. 26 However, none of the tablet and suspension excipients used in this study (Table 1) Finally, differences could also be due to the slightly different dosage between the tablet and suspension formulations used. In fact, some studies have shown results of nonlinear kinetics for AMX, 28 which could help to justify the difference between the tablets and suspension observed in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Another possible explanation for the differences observed in the present study could be due to the differences in the excipients between the two formulations. It is known that some excipients and vehicles, such as polyethylene glycol 400 (PEG 400), mannitol and xylitol, among others, may decrease the GI transit time, resulting in decreased drug bioavailability . However, none of the tablet and suspension excipients used in this study (Table ) are known to produce this effect.…”
Section: Discussionmentioning
confidence: 93%
“…PEG 400 is osmotically active and will "hold" fluid in the lumen of the intestine, leading to an increase in bulk fluid volume, which in turn stimulates peristalsis and hence transit. No such effects on transit have been noted with other commonly used solubility enhancing excipients such as propylene glycol, vitamin E-TPGS, Labrasol and Capmul MCM in man or dog (5,6).…”
Section: Introductionmentioning
confidence: 97%